2019
DOI: 10.3390/molecules24213851
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oil from Pinus Koraiensis Pinecones Inhibits Gastric Cancer Cells via the HIPPO/YAP Signaling Pathway

Abstract: Pinecone is a traditional folk herb, which has been used in China for many years. In this paper, the essential oil from Pinus koraiensis pinecones (PEO) was obtained by hydrodistillation and 41 compounds were identified by gas chromatography–mass spectrometry (GC-MS), mainly including α-Pinene (40.91%), Limonene (24.82%), and β-Pinene (7.04%). The purpose of this study was to investigate the anti-tumor activity of PEO on MGC-803 cells and its mechanism. Anti-tumor experiments in vitro showed PEO could signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 59 publications
(66 reference statements)
0
18
0
Order By: Relevance
“…We demonstrated that PMEO induces apoptosis in human prostate cancer cells without affecting the viability of non-transformed human fibroblasts. The anticancer activities of EOs from two other pine species were described earlier [ 36 , 37 ]. Ren et al (2018) reported that Pinus densiflora needles EO suppressed tumor growth in an MCF-7 xenograft mouse model by regulating the AMPK/mTOR signaling pathway [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated that PMEO induces apoptosis in human prostate cancer cells without affecting the viability of non-transformed human fibroblasts. The anticancer activities of EOs from two other pine species were described earlier [ 36 , 37 ]. Ren et al (2018) reported that Pinus densiflora needles EO suppressed tumor growth in an MCF-7 xenograft mouse model by regulating the AMPK/mTOR signaling pathway [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The EO from Pinus koraiensis (Pinaceae) also arrested the cell cycle in the G 2 /M phase and induced cell death in gastric adenocarcinoma MGC-803 cells. The main chemical constituents were α-pinene, limonene and β-pinene [37]. The EO from the leaves of Melaleuca alternifolia (Myrtaceae) arrested the cell cycle in the G 2 /M phase, causing cell death in human melanoma A-375 cells and squamous cell carcinoma HEp-2 cells [38].…”
Section: Discussionmentioning
confidence: 99%
“…Pinenes have good anticancer activity, arrest the cell cycle in the G2/M phase, and inhibit hepatoma cell proliferation [ 14 ]. Pinus koraiensis essential oils, mainly consisting of α-pinene, stop the proliferation and migration of human gastric carcinoma cells (MGC-803) and induce apoptosis [ 89 ]. This is due to its effect on the Hippo signaling pathway, known as the tumor suppressor, which has been extensively studied [ 112 ].…”
Section: The Future Role Of Gymnosperms In Cancer Therapymentioning
confidence: 99%
“…In this pathway, the phosphorylation of YAP occurs and inhibits the migration and proliferation of tumor cells [ 113 ]. α-Pinene can decrease the expression of YAP, leading to the inhibition of cancer cells and the induction of apoptosis [ 89 ].…”
Section: The Future Role Of Gymnosperms In Cancer Therapymentioning
confidence: 99%